Outbred animal stock quantitative trait loci may be finely mapped using this approach. - REDDY, SWAPNA; JYOTHI, VIJAYA (The journal of contemporary issues in business and government, 2020)
Because of the huge effect sizes seen in crosses between inbred strains, high-resolution mapping of quantitative trait loci (QTL) in animals has proven to be problematic. Each has a little impact. We've discovered that mice are more scared than previously thought. small-effect QTLs may be fine-mapped in a genetically diverse population the stock market (HS). This is a great overall technique for fine-tuning. given that QTLs are found in crosses between inbreds, the mapping process The HS may be used to identify the strains that generated theHS. Weshow Only two of the five candidates are found in this study using a single-marker association analysis. In the HS, QTLs are predicted to be segregated, which presumably restricts the number of QTLs. For precise mapping, strategy is crucial. With this issue, we come up with a novel solution. allele descent probabilities may be calculated using multipoint analysis. from each of the HS's ancestors. Pedigrees are not used in the study. but instead calls for data on the haplotypes of the HS's founding fathers. We were able to locate all three previously unidentified loci using this strategy. Chr. 1 logP 4.9, Chr. 10 logP 6.0, and Chr. 15 logP 4.0 [chromosomes]. Wesingle- marker association fails because of this reason its inability to discriminate between the phenotypic impacts of competing QTLs when both markers are found on the same allele of the gene We've created a new product. QTL mapping in genetically diverse populations using a robust technique genetic testing on animals and claim that it is now cost-effective simultaneous, high-resolution examination of several complicated characteristics a group of mice